Preparation of Saccharomycopsis fibuligera Fuqu and Its Application in the Production of Xiaoqu Baijiu - LIU Xiao, HUANG Zhiguo, WEI Chunhui, REN Zhiqiang, XIE Jun, DENG Jie (Shipin Kexue)
In order to increase the content of ethyl acetate in Xiaoqu Baijiu, a strain of Saccharomycopsis fibuligera M1 with strong ester-producing capacity isolated from Daqu was used as the starting strain for preparing Fuqu (M1-Fuqu), which was subsequently used for the brewing of Xiaoqu Baijiu. The effect of enhanced fermentation of M1-Fuqu on volatile compounds of Xiaoqu Baijiu. The results showed that the optimal cultivation conditions for M1-Fuqu were 40% of water content, 28 ℃ of cultivation temperature, 6 mmol/100 g of initial acidity, and 48 h of cultivation time. The brewing experiments showed that the contents of acetic acid and ethyl acetate significantly increased (P < 0.05), and the contents of isobutanol and isoamyl alcohol significantly decreased in the M1-Fuqu group compared with the control group (traditional Xiaoqu Baijiu) (P < 0.01). Differences in the microbial community structure of fermented grains were observed between the control and experimental groups during the fermentation process, and the relative abundance of S. fibuligera and Weissella significantly increased in the experimental group. In addition, PICRUSt2 functional prediction confirmed that the abundance of enzymes involved in the metabolism of acetic acid and ethyl acetate was higher in the experimental group than in the control group during the fermentation process. In conclusion, the present study highlighted that the application of S. fibuligera M1-added Fuqu could increase the content of ethyl acetate in Xiaoqu Baijiu, which is reference significance for the quality improvement of Xiaoqu Baijiu.